2018
DOI: 10.1080/13218719.2018.1477633
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in spontaneous trait judgments from facial appearance

Abstract: We tested whether there are age-related declines in detecting cues to trustworthiness, a skill that has been demonstrated to be rapid and automatic in younger adults. Young (M age D 21.2 years) and older (M age D 70.15 years) adults made criminal appearance judgments to unfamiliar faces, which were presented at a duration of 100, 500 or 1,000 ms. Participants' response times and judgment confidence were recorded. Older were poorer than young adults at judging trustworthiness at 100 ms, and were slower overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 35 publications
0
7
1
Order By: Relevance
“…The dominance and trustworthiness indices were very strongly correlated, r (93) = −.82, p = .03, and a factor analysis confirmed that they all loaded onto the same factor (see Supplemental File for details). 1 Indeed, a recent data-driven approach found that these two dimensions are strongly linked to perceptions of a criminal appearance (Funk et al, 2017; c.f., Smailes et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dominance and trustworthiness indices were very strongly correlated, r (93) = −.82, p = .03, and a factor analysis confirmed that they all loaded onto the same factor (see Supplemental File for details). 1 Indeed, a recent data-driven approach found that these two dimensions are strongly linked to perceptions of a criminal appearance (Funk et al, 2017; c.f., Smailes et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The face perception literature has consistently demonstrated that people regularly make social judgments based on others’ appearances without any other supporting information, such as actual behaviors that would be more diagnostic of their internal states (Langlois et al, 2000). For instance, perceivers are quick to make judgments about an individual’s trustworthiness and criminality on the basis of their face alone (Jaeger et al, 2019; Klatt et al, 2016; Smailes et al, 2018). These face-based judgments are problematic because they are largely inaccurate, yet they have direct implications for a variety of outcomes (see Todorov et al, 2015).…”
Section: The Power Of Facial Characteristicsmentioning
confidence: 99%
“…Given that in comparison with young adults, older adults tend to show a positivity bias where they interpret untrustworthy faces as more trustworthy and approachable, and do not differ in judgements of trustworthiness from faces for young and older adults (Castle et al, 2012;Smailes et al, 2018); we imply that facial cues about negatively perceived traits are known to be better remembered. In relation to facial memory, studies have reported that negative traits such as untrustworthiness are more memorable from faces (Bayliss & Tipper, 2006;Mealey, Daood, & Krage, 1996;.…”
Section: The Impact Of Age On Implicit Personality Judgementsmentioning
confidence: 79%
“…Furthermore, studies on implicit and explicit memory have suggested that older adults tend to be better than younger adults with implicit memory (Gopie et al, 2011;Light & Singh, 1987). Additionally, studies have also reported that older adults tend to show a positivity bias where they interpret untrustworthy faces as more trustworthy and approachable in comparison with young adults and the ratings did not differ for judgements of trustworthiness across ages (Castle et al, 2012;Smailes et al, 2018). It has also been suggested that older adults remember positive information better than negative information (e.g., Charles, Mather, & Carstensen., 2003;Mather & Cartensen., 2003).…”
Section: The Impact Of Age On Implicit Personality Judgementsmentioning
confidence: 99%
See 1 more Smart Citation